Community Assistance with Catering Training in the Orphanage Children Empowerment Program - Marwan, Syaiful; Fazis, Muhammad; Haris, Venny; Mastanora, Refika; Aris, Sarmen (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2022)
Orphanage assistance is carried out, in an effort to improve the feasibility of orphanage services inthe welfare of children. The orphanage children provide the best services and improvements to prosper andincrease individual independence. The service process is carried out using the Participatory Action Research(PAR) methodology or better known as conducting to promote understanding of community life situationsas a basis for action. The activities carried out are training activities in cooking or otherwise known ascatering for orphanage children. Catering activities for orphanage children were carried out with as many as20 participants and also attended by the caretaker/manager of the orphanage. The material presented is toprovide skills in processing religious food raw materials as a source of the productive economy, to traingradually to have entrepreneurial and business competencies, and to develop children as human resourcesso that they are able to create job opportunities for themselves and others. Participation of children andorphanage managers are actively involved in an effort to maximize the results achieved